PENERAPAN PEMBELAJARAN BERBASIS GENRE DAN KARTU DOMINO UNTUK MENINGKATKAN PRESTASI MENULIS PUISI SISWA - Iqbakva Demas W; Afita Dwi; Hannifia Dalia; Onok Yayang Pamungkas; Laily Nurlina (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This study aims to explore the effectiveness of implementing a genre-based learning approach using domino card media to improve student achievement in Indonesian language subjects, particularly in poetry writing for eighth-grade students at MTs (Islamic Junior High School). Poetry writing often poses challenges for students due to a lack of understanding of poetic structure and low motivation to be creative. The genre-based approach is expected to help students understand various elements of poetry, such as structure, figurative language, and the social context behind the text, enabling them to express ideas and emotions more effectively. Domino card media is used as an interactive tool to stimulate students’ creativity and assist them in finding inspiration for writing. This research employs a classroom action research (CAR) design conducted in two cycles. The subjects of the study are eighth-grade students. The results show a significant improvement in student achievement. The average test score increased from 68.00 in the pre-cycle to 77.00 in Cycle II. The percentage of classical learning mastery also rose, from 70.00% to 83.00%. Teacher performance also improved. The planning score increased from 89.00 to 91.00, and the implementation score rose from 88.00 to 90.00. These findings indicate that the genre-based approach combined with domino card media is effective in enhancing the quality of learning. Although the results are positive, there is still room for further improvement, and follow-up plans should focus on sustainable development in the teaching and learning process.